2014
DOI: 10.1200/jco.2013.54.9329
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age With Survival in Patients With Metastatic Colorectal Cancer: Analysis From the ARCAD Clinical Trials Program

Abstract: Purpose This study addressed whether age is prognostic for overall survival (OS) or progression-free survival (PFS) in patients with metastatic colorectal cancer (mCRC). Patients and Methods A total of 20,023 patients from 24 first-line clinical trials in the ARCAD (Aide et Recherche en Cancérologie Digestive) database were analyzed. Primary age effects and interactions with age, sex, performance status (PS), and metastatic site were modeled using Cox proportional hazards stratified by treatment arm within s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 14 publications
11
120
3
1
Order By: Relevance
“…Because younger cancer patients are, in general, more likely than older patients to receive aggressive antineoplastic therapy due to higher performance status, fewer comorbidities, and more willingness to accept risk, the superior survival among younger CRC patients in the TCR and other population-based studies may simply reflect selection bias rather than inherent tumor biology 38,39 . Indeed, a pooled analysis of 20,023 patients enrolled in randomized controlled trials for first-line stage IV CRC 40 revealed that, after adjustment for performance status and sex, the youngest patients (those near 18 years old) had inferior overall and progression-free survival when compared to middle-aged patients (those near 57 years old), especially during the first year of treatment. These data suggest more aggressive tumor biology in young patients, who, in the context of these highly controlled trials, would have received the same treatment as their older counterparts 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Because younger cancer patients are, in general, more likely than older patients to receive aggressive antineoplastic therapy due to higher performance status, fewer comorbidities, and more willingness to accept risk, the superior survival among younger CRC patients in the TCR and other population-based studies may simply reflect selection bias rather than inherent tumor biology 38,39 . Indeed, a pooled analysis of 20,023 patients enrolled in randomized controlled trials for first-line stage IV CRC 40 revealed that, after adjustment for performance status and sex, the youngest patients (those near 18 years old) had inferior overall and progression-free survival when compared to middle-aged patients (those near 57 years old), especially during the first year of treatment. These data suggest more aggressive tumor biology in young patients, who, in the context of these highly controlled trials, would have received the same treatment as their older counterparts 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that young patients presenting with advanced CRC have a higher risk of long-term mortality compared to older patients (Forbes et al, 2010). An analysis of 20,034 patients in 24 phase III clinical trials, showed that the young CRC patients had 30% increased risk of death and 28% increased risk of disease progression compared to middle-aged patients (Lieu, 2013). Genetic and dietary factors were suggested to play a role in this poor outcome (Arafa et al, 2011;Zandonai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that, observational studies are essential to identify whether practice has changed appropriately, to document harms of therapy in a wider population, in patients of different age and with different comorbidities and to determine whether patients in routine practice are reaching the expected outcomes [17][18][19] with future science group www.futuremedicine.com the expected toxicity. However, when multiples RCTs within one tumor type and comparing over decades and worldwide different treatment agents, classes and subpopulations, are observed in a pooled analysis [20][21][22], the best of both research regimens is reached: high amount of patient's variability with high data quality.…”
Section: Practice Pointsmentioning
confidence: 99%